Implementasi Pembelajaran IPAS Berbasis Kurikulum Merdeka Belajar pada Siswa Kelas V - Ummi Nihayatul Fadlilah; Khamdun Khamdun; Imaniar Purbasari (Journal on Education, 2024)
The independent learning curriculum is given to teachers to freely develop learning tools that suit students' needs and interests. The aim of this research is to analyze science learning based on the independent learning curriculum and the obstacles in science learning based on the independent learning curriculum. This research was carried out at SD Negeri Dengkek 01 Pati in February 2024 with the research subjects being fifth grade students and educators, taken from students' learning styles during learning activities using data collection techniques obtained through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and data withdrawal. The validity of the research data uses a credibility test with triangulation techniques. The research results show that science and science learning based on the independent learning curriculum is quite conducive. In preparation for independent curriculum-based science and science learning, teachers take part in preparation training for implementing the independent learning curriculum, compiling teaching modules tailored to student needs, creating learning media. In implementing learning, teachers use lecture, discussion and presentation methods. When learning Indonesian Map material in the independent curriculum, students have creativity, critical thinking, collaboration, and communication skills.